Republic of Colombia : Mitigating Environmental Degradation to Foster Growth and Reduce Inequality - World Bank (World Bank, Washington, DC, 2020)
Over the last five decades, Colombia has made substantial progress in protecting its environment. This includes restructuring its legal and regulatory landscape, undertaking policy initiatives, and strengthening its capacity for protecting and managing its natural resources and environmental quality, and establishing a system of national parks and forestry reserves that covers more than a quarter of the country. Colombia's environmental management framework has focused on three main environmental priorities: (a) river basin management and conservation of water resources, (b) reforestation, and (c) conservation o f biodiversity. The analysis of the cost of environmental degradation conducted as part of the Country Environmental Analysis (CEA), shows that the most costly problems associated with environmental degradation are urban and indoor air pollution; inadequate water supply, sanitation and hygiene; natural disasters (such as flooding and landslides); and land degradation. The burden of these costs falls most heavily on vulnerable segments of the population, especially poor children under age five. The effects of environmental degradation associated with these principal causes are estimated to cost more than 3.7 percent of Gross Domestic Product (GDP), mainly due to increased mortality and morbidity and decreased productivity. To identify alternatives aimed at abating the cost of environmental degradation, this CEA examines institutional and policy issues in the functioning of the country's environmental management system and suggests some cost-effective interventions.